Conductive Polymer Spark Gap Igniters. Issue 10 (13th August 2021) - McConnell, Miranda P.; Murray, Allison K.; Boudouris, Bryan W.; Gunduz, I. Emre; Son, Steven F.; Chiu, George T.‐C.; Rhoads, Jeffrey F.
Abstract: Electrodes fabricated from electronically active polymers offer some benefits over those fabricated with common metals, including an appreciable resistance to corrosion and lower density. These benefits, and potentially others, manifest the advantages of using conductive polymers in lieu of metals for the mass production of ignition systems. In this work, spark gap igniters were fabricated using a potentially low‐cost, roll‐to‐roll compatible process utilizing the doped conductive polymer polyaniline as the electrode material. Subsequently, nanothermite was printed on the spark gap igniters between the organic leads and ignited using a high voltage source to demonstrate the effectiveness of the device. All of the igniters successfully fired with a mean spark over voltage of 3.14 kV. In addition, all of the igniters with deposited nanothermite successfully ignited the material. Accordingly, this work outlines the materials and processes required to develop organic‐based spark gap igniters and establishes a baseline for future work related to the metal‐free ignition of energetic materials. Abstract :